2016
DOI: 10.1146/annurev-economics-080315-015356
|View full text |Cite
|
Sign up to set email alerts
|

Econometric Analysis of Large Factor Models

Abstract: Large factor models use a few latent factors to characterize the co-movement of economic variables in a high dimensional data set. High dimensionality brings challenge as well as new insight into the advancement of econometric theory. Due to its ability to effectively summarize information in large data sets, factor models have been increasingly used in economics and finance. The factors, being estimated from the high dimensional data, can help to improve forecast, provide efficient instruments, control for no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 125 publications
0
36
0
Order By: Relevance
“…Moon & Weidner (2017) showed that the FE least squares estimator of δ suffers from a Nickell (1981) type incidental parameter bias when the covariates are predetermined, even when the model is correctly specified. We refer to Bai & Wang (2016) for a recent review, and to Pesaran (2006) and Chudik & Pesaran (2015b) for alternative estimation methods of factor models.…”
Section: Multivariate Fixed Effectsmentioning
confidence: 99%
“…Moon & Weidner (2017) showed that the FE least squares estimator of δ suffers from a Nickell (1981) type incidental parameter bias when the covariates are predetermined, even when the model is correctly specified. We refer to Bai & Wang (2016) for a recent review, and to Pesaran (2006) and Chudik & Pesaran (2015b) for alternative estimation methods of factor models.…”
Section: Multivariate Fixed Effectsmentioning
confidence: 99%
“…Moon & Weidner (2017) showed that the FE least squares estimator of δ suffers from a Nickell (1981) type incidental parameter bias when the covariates are predetermined, even when the model is correctly specified. We refer to Bai & Wang (2016) for a recent review on this model.…”
Section: Multivariate Fixed Effectsmentioning
confidence: 99%
“…Moon & Weidner (2017) showed that the FE least squares estimator of δ suffers from a Nickell (1981) type incidental parameter bias when the covariates are predetermined, even when the model is correctly specified. We refer to Bai & Wang (2016) for a recent review, and to Pesaran (2006) and Chudik & Pesaran (2015b) for alternative estimation methods of factor models.…”
Section: Multivariate Fixed Effectsmentioning
confidence: 99%